54‐5: New Technologies for Colouring in Displays. Issue 1 (29th May 2019) - Kim, Yohan; Geßner, André; Heyne, Benjamin; Choi, Hyung Seok; Wedel, Armin
Abstract : Colloidal quantum dots (QDs)‐based light‐emitting diodes (QLEDs) has been actively researched due to the potential impacts to the display and lighting industry base on the unique properties of QDs itself such as size‐dependent bandgap tunability, narrow emission spectrum, and low‐cost solution‐based processing. However, the most of promising results in the past used cadmium (Cd) contained II‐VI semiconductor nanocrystals. Therefore, a considerable future task is to substitute QDs with less toxic materials. InP‐based QDs is a promising material for colour‐saturated display among the III‐V semiconductor nanocrystals and it has been already applied in conventional and inverted QLED structure.